2002
DOI: 10.1083/jcb.200208112
|View full text |Cite
|
Sign up to set email alerts
|

VCIP135, a novel essential factor for p97/p47-mediated membrane fusion, is required for Golgi and ER assembly in vivo

Abstract: NSF and p97 are ATPases required for the heterotypic fusion of transport vesicles with their target membranes and the homotypic fusion of organelles. NSF uses ATP hydrolysis to dissociate NSF/SNAPs/SNAREs complexes, separating the v- and t-SNAREs, which are then primed for subsequent rounds of fusion. In contrast, p97 does not dissociate the p97/p47/SNARE complex even in the presence of ATP. Now we have identified a novel essential factor for p97/p47-mediated membrane fusion, named VCIP135 (valosin-containing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
236
2
6

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 194 publications
(254 citation statements)
references
References 33 publications
10
236
2
6
Order By: Relevance
“…Subsequent work has confirmed the role of p97 in the dynamics of ER architecture [15,16], but also indicates the participation of additional mechanisms. Thus, antibodies against p97 or its cofactors only partially disrupt ER organization in living cells [17] or in cell-free reconstituted systems [18]. Moreover, S. cerevisiae Cdc48 mutants appear to have normal ER organization [19].…”
Section: Homotypic Fusionmentioning
confidence: 99%
“…Subsequent work has confirmed the role of p97 in the dynamics of ER architecture [15,16], but also indicates the participation of additional mechanisms. Thus, antibodies against p97 or its cofactors only partially disrupt ER organization in living cells [17] or in cell-free reconstituted systems [18]. Moreover, S. cerevisiae Cdc48 mutants appear to have normal ER organization [19].…”
Section: Homotypic Fusionmentioning
confidence: 99%
“…More recently, Kondo and coworkers have shown that the p97 adapter proteins p47 and VCIP135 are required in vivo for reassembly of the Golgi apparatus and formation of the ER network upon exit from mitosis (Uchiyama et al, 2002, Uchiyama et al, 2003. Although these studies may point to a specific role for p97 in membrane fusion, both adaptor proteins are also directly linked to ubiquitin pathways.…”
Section: P97 and Membrane Fusionmentioning
confidence: 99%
“…Article and publication date are available at www.molbiolcell.org/cgi/doi/10.1091/mbc. E03-02-0097.1997), Ufd1/Npl4 (Meyer et al, 2000(Meyer et al, , 2002, VCIP135 (Uchiyama et al, 2002), and SVIP (Nagahama et al, 2003).…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations